2006
DOI: 10.1207/s15327914nc5501_7
|View full text |Cite
|
Sign up to set email alerts
|

Safety, Tolerance, and Metabolism of Broccoli Sprout Glucosinolates and Isothiocyanates: A Clinical Phase I Study

Abstract: Broccoli sprouts are widely consumed in many parts of the world. There have been no reported concerns with respect to their tolerance and safety in humans. A formal phase I study of safety, tolerance, and pharmacokinetics appeared justified because these sprouts are being used as vehicles for the delivery of the glucosinolate glucoraphanin and its cognate isothiocyanate sulforaphane [1-isothiocyanato-(4R)-(methylsulfinyl)butane] in clinical trials. Such trials have been designed to evaluate protective efficacy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
283
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 304 publications
(300 citation statements)
references
References 20 publications
15
283
0
2
Order By: Relevance
“…In this study, we found that sulforaphane has strong analgesic effects on SNT-induced pain hypersensitivity, suggesting additional therapeutic potential for this molecule in the treatment of neuropathic pain. Its analgesic efficacy observed postinjury and its safety verified in a clinical trial (24) further underscore its therapeutic potential.…”
Section: Discussionmentioning
confidence: 87%
“…In this study, we found that sulforaphane has strong analgesic effects on SNT-induced pain hypersensitivity, suggesting additional therapeutic potential for this molecule in the treatment of neuropathic pain. Its analgesic efficacy observed postinjury and its safety verified in a clinical trial (24) further underscore its therapeutic potential.…”
Section: Discussionmentioning
confidence: 87%
“…Glucosinolates and isothiocyanates could be interesting candidates for such strategies. They have been investigated in clinical trials with no significant reported toxicity (31)(32)(33). However, only sulforaphane precursors such as purified glucosinolates or broccoli sprouts and not sulforaphane are currently in intervention trials because sulforaphane is highly unstable in its free form (34).…”
Section: Introductionmentioning
confidence: 99%
“…It is responsible for DNA fragmentation and some of the distinct morphological features of apoptotic cells such as shrinkage and budding. 32 The results of light microscopy to determine cell morphology proved that apoptotic changes were independent of caspase-3, which is lacking in MCF-7 cells. From these results one can suggest that apoptosis induced by Euphorbia hirta leaves extract does not correlate with the activation of caspase-3 but may activate different apoptotic pathways and other effector caspases such as caspase-6 or -7.…”
Section: Acknowledgementmentioning
confidence: 97%
“…38 Or that some cell lines, such as MCF-7, can undergo apoptosis without showing DNA fragmentation due to lack of caspase-3 which is responsible for this feature. 32 Another explanation may be that the long incubation time of DNA led to lyses of a substantial part of the cell population. The smear pattern was also observed in the controls for both cell types that were treated with 0.1% DMSO for 72 h, which confirms the previous explanation.…”
Section: Acknowledgementmentioning
confidence: 99%